PdPc Strategies and Techniques for Handling Special Needs Students with Hearing Impairment in Inclusive Education - Husin, Mohd Razimi; Nor Rahmat, Aeidah Farhana; Rosle, Afina Fashihah; Mohamad Hassan, Fairuz Syakirah; Mat Nawi, Farah Shamimi; Abiraham, Melisa Abraham; Abd Rahman, Noorshaqilah; Mohamad Razman, Nurul Atikah; Khairulanuar, Nur Batrisyia Syazwana; Hassan Basari, Nur Hadirah; Haziqah Suhaili, Umi Syahzani; Malik, Siti Fatimah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Setiap individu mempunyai hak yang sama terhadap peluang pendidikan, termasuklah mereka yang mempunyai ketidakupayaan (Murid Berkeperluan Khas). Dijelaskan bahwa 58% daripada pelajar pekak pendengaran atau berketidakupayaan pendengaran di Malaysia telah mendaftar dalam pendidikan inklusif. Pendidikan inklusif membuktikan pendekatan pihak Kementerian Pelajaran Malaysia berusaha untuk memberi hak sama rata kepada setiap warga dan rakyat Malaysia. Dapatan kajian menunjukkan bahawa tiada pedagogi yang khusus untuk MBK kecuali untuk murid kurang upaya pendengaran atau penglihatan. Namun, proses pengajaran dan pembelajaran yang dijalankan oleh guru menentukan kesesuaian pengajaran dari segi hasil yang dapat dilihat oleh setiap pelajar MBK. Antara strategi pengajaran guru dalam pendidikan inklusif ialah mengenal dan mengambil tahu tentang murid MBK serta menyediakan proses PdP yang berpusat kepada setiap murid termasuk murid MBK. PdPc Strategies and Techniques for Handling Special Needs Students with Hearing Impairment in Inclusive Education Abstract: Every individual has the same right to educational opportunities, including those with disabilities (Students with Special Needs). It was explained that 58% of deaf or hard of hearing students in Malaysia have enrolled in inclusive education. Inclusive education proves the approach of the Malaysian Ministry of Education to give equal rights to every citizen of Malaysia. The findings of the study show that there is no specific pedagogy for Students with Special Needs except for students with hearing or visual disabilities. However, the teaching and learning process carried out by teachers determines the appropriateness of teaching in terms of results that can be seen by every Students with Special Needs student. Among the teaching strategies of teachers in inclusive education is to get to know and learn about Students with Special Needs students as well as provide a Teaching & Learning process centered on each student including Students with Special Needs students. Keywords: Student Centered Learning, Students with Special Needs, Teaching and Learning.